Study Pattern and Need for Learning Management System for Pharmacy Practice Students of Select Colleges in South India: A Pilot Study - A E, Arun; K, Kannan; RH, ShobhaRani; K N, Sundaresh; H S, Shekar; S, Ramjan (Indian Journal of Pharmacy Practice)
Objective: To do a pilot study to understand the study habits of the post-graduation (PG) pharmacy practice students in India and their perspective on the use of a Learning Management System (LMS) in line with the current system of education to meet the industrial requirements in the Indian scenario. Materials and Method: The researchers administered an open labeled questionnaire to understand students study pattern, expectations from the use of a LMS to support their study goals. Consent was obtained from the students to use the data provided for deriving inferences for research purposes. Data was collected from all the students belonging to two premier private pharmacy colleges in Bangalore, India and converted to graphical representations using Microsoft excel to provide simple percentages. Results: The current trend in pharmacy education system shows that the PG students study/learn mostly during the internal and external examinations. This is a due to the pressure of doing well in the examination. This study also showed that the students learn mostly from discussions, seminars and examinations. It was observed that the students wanted a proper orientation program that will train them in the best way to complete the PG course and to know of the options that will be available for them once they have completed the course. 82% of the students were excited to have the support of LMS to provide them with a dashboard view of their performance in comparison with the rest of the class. This excitement can be related to the goal of the student to be competitive in the industry to get better opportunities if they can do well in their PG course. Conclusion: This pilot study should be considered as an eye opener, as it shows that the pharmacy practice PG student's needs continuous support in terms of online lectures, research support, practical training, etc. which is currently unavailable. This support can easily be provided with the use of LMS that will support the students round the clock with guaranteed benefits as shown from studies conducted around the world in pharmacy colleges.
Keywords: Post-graduation; Pharmacy Practice; Learning; Management; Study Pattern